PENGARUH BRAND IMAGE DAN SIKAP TERHADAP IKLAN SAMPO CLEAR MEN PADA SWITCHING BEHAVIOR KONSUMEN - , Waode Pristanti Nuri Rachmawati, Dr. Ike Janita Dewi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to determine the effect of variable shampoo brand image and attitude toward the ad on the switching behavior of consumers. The hypothesis proposed in this study were (1) Clear shampoo brand image has a positive effect on Clear Men shampoo brand image, (2) Attitude to Clear Men shampoo advertisements has a positive influence on Clear Men Shampoo Brand image, (3) Brand image Clear Men Shampoo has a positive influence to switching behavior on the consumer and, (4) There is a difference between the Clear Men shampoo brand image to consumers who buy their own shampoo products and consumers who acquire Clear shampoo products from others. This study uses purposive sampling method because the author has certain criteria for the respondents that are tailored to the research design. Respondents in this study were men who numbered 120 persons consisting of consumers who act as buyers of 60 people and respondents who use the Clear Men shampoo as many as 60 people. Research result with linear regression model showed Clear Brand image has a value of 0.223 with beta coefficient of t statistic 2.582 (p = 0.011 <0.05) and attitude toward the ad has a beta coefficient value of 0.315 with t statistic 3.653 (p = 0.000 <0.05) which means that the variable Clear shampoo brand image and attitude toward the ad has a positive effect on brand image variables until Clear Men. Then linear regression analysis Clear Men shampoo brand image with Switching behavior indicates Clear Men Brand image has a value of 0.519 with a beta coefficient t statistic 6.602 (p = 0.000 <0.05) which means Clear Men shampoo brand image has a positive effect on the switching consumers behavior. Analysis result of two different averages in the Clear shampoo brand image showed no differences in brand image to consumers who buy their own with the consumers who receive product from others.